A new species-group of Clubiona Latreille, 1804 and descriptions of four new species from Borneo (Araneae, Clubionidae) - Pakawin Dankittipakul (2018)
A new species-group, the apiculata-group, of Clubiona Latreille, 1804 is erected to accommodate four new spider species closely related to the hystrix- and pahilistapyasea-groups from tropical forests of Borneo. These new taxa are Clubiona apiculata sp. nov., Clubiona conica sp. nov., Clubiona cylindriformis sp. nov. and Clubiona cultrata sp. nov.http://zoobank.org/urn:lsid:zoobank.org:pub:6063425C-2445-4173-91B7-0F730B30708F. © 2014 © 2014 Taylor & Francis.